Risk score to predict biliary leakage after elective liver resection. Issue 1 (13th November 2017) - Mohkam, K.; Farges, O.; Vibert, E.; Soubrane, O.; Adam, R.; Pruvot, F.‐R.; Regimbeau, J.‐M.; Adham, M.; Boleslawski, E.; Mabrut, J.‐Y.; ,
Abstract : Background: Biliary leakage remains a major cause of morbidity after liver resection. Previous prognostic studies of posthepatectomy biliary leakage (PHBL) lacked power, population homogeneity, and model validation. The present study aimed to develop a risk score for predicting severe PHBL. Methods: In this multicentre observational study, patients who underwent liver resection without hepaticojejunostomy in one of nine tertiary centres between 2012 and 2015 were randomly assigned to a development or validation cohort in a 2 : 1 ratio. A model predicting severe PHBL (International Study Group of Liver Surgery grade B/C) was developed and further validated. Results: A total of 2218 procedures were included. PHBL of any severity and severe PHBL occurred in 141 (6·4 per cent) and 92 (4·1 per cent) patients respectively. In the development cohort (1475 patients), multivariable analysis identified blood loss of at least 500 ml, liver remnant ischaemia time 45 min or more, anatomical resection including segment VIII, transection along the right aspect of the left intersectional plane, and associating liver partition and portal vein ligation for staged hepatectomy as predictors of severe PHBL. A risk score (ranging from 0 to 5) was built using the development cohort (area under the receiver operating characteristic curve (AUROC) 0·79, 95 per cent c.i. 0·74 to 0·85) and tested successfully in the validation cohort (AUROC 0·70, 0·60 to 0·80). A score of at least 3 predicted an increase in severe PHBL (19·4 versus 2·6 per cent in the development cohort, P < 0·001; 15 versus 3·1 per cent in the validation cohort, P < 0·001). Conclusion: The present risk score reliably predicts severe PHBL. It represents a multi‐institutionally validated prognostic tool that can be used to identify a subset of patients at high risk of severe PHBL after elective hepatectomy. Abstract : Multi‐institutionally validated prognostic tool